Pengaruh Ekstrak Daun Kopi Robusta (Coffea canephora Pierre ex A. Froehner) terhadap Kualitas Spermatozoa Mencit (Mus musculus L.) Yang Terpapar Asap Rokok. - I Komang Alit Saputra; Ni Gusti Ayu Manik Ermayanti; A.A. S. A. Sukmaningsih (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
This study aims to determine the effect of given robusta coffee (Coffea canephora Pierre ex A. Froehner) leaf extract on the spermatozoa quality of mice (Mus musculus L.) exposed to cigarette smoke. The experiment was using a completely randomized design (CRD) with five treatments and each consisted of six mice as replications. Each treatment was K- (without exposure to cigarette smoke), K+ (exposure to cigarette smoke + 0.5% Na-CMC), P1 (exposure to cigarette smoke + Robusta coffee leaf extract at a dose of 60 mg/kgbw), P2 (exposure to cigarette smoke + Robusta coffee leaf extract at a dose of 120 mg/kgbw) and P3 (exposure to cigarette smoke + Robusta coffee leaf extract at a dose of 180 mg/kgbw). On the 36th day, mice were taken down by anesthesia and followed by surgery to collect spermatozoa. The parameters for this observation were the concentration, motility, viability, morphology, and integrity of the spermatozoa membrane. The data obtained were analyzed statistically with One Way Anova and further tested with DMRT. The results showed that the treatment of robusta coffee leaf exstract in mice exposed to cigarette smoke had a significant effect (P<0,05) on the quality of spermatozoa.